Assessing the adaptive reuse of old industrial buildings: applying Maslow’s hierarchy of needs and fuzzy comprehensive evaluation method - Zheng, Xuesen (2023)
In many cases, the purpose of reusing old industrial buildings is to meet the needs of the new generation. Converting a building that had a particular function and is unfamiliar to the public to a civic building is a great challenge. Significantly, the public’s curiosity towards a special-purpose industrial building alone is not enough to give the building a long life following its conversion and regeneration. To be sustainable in public life, the design of reused old industrial buildings should also meet the needs of users. To do so, this research will draw upon Maslow’s Hierarchy of Needs (Maslow, 1943), and translates this psychological theory into the field of architecture to develop an assessment framework for the reuse of old industrial buildings. This assessment framework will be combined with the fuzzy mathematical model to enable a quantitative assessment of reused old industrial buildings. In doing so, the thesis focuses upon Shanghai 1933 Old Millfun, and Dalian Industrial Culture Exhibition Hall as case studies for its demonstration. The cases demonstrate how the assessment methodology created by this study can be used, not only to show the framework’s application, but also to make recommendations for the future development of examed cases. The research achieves a multidisciplinary combination, among which, the integration with psychology makes the building more human; the mathematics makes the building assessment comparable. Furthermore, the findings of the assessment framework serve as a reminder of the design of similar buildings in the future, thus enhancing the publicness of the project.